2007
DOI: 10.1163/156854007780440902
|View full text |Cite
|
Sign up to set email alerts
|

On two new Anostraca species (Branchiopoda) from Turkey: Chirocephalus anatolicus sp. nov. and Chirocephalus cupreus sp. nov.

Abstract: Chirocephalus anatolicus and C. cupreus, two new fairy shrimp species belonging to the "bairdi" and "diaphanus" group , respectively, are described and discussed in detail.These new species were collected in Turkey from temporary pools on the Anatolian plateau. A number of morphological features (related to the first antenna, mandibles, first maxilla, and notopods P6-P8) are also illustrated and discussed in relation to their taxonomic and phylogenetic importance. The same holds for some peculiarities of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Four species were attributed to the bairdi species-group, the remaining were attributed to the diaphanus species-group or are impossible to be attributed to any of the traditional species-groups (present work). The present work questions the monophyly of the bairdi species-group, thus calling into question also the hypothesis raised by Cottarelli et al (2007Cottarelli et al ( , 2010, who suggested the role of Asiatic Turkey as a possible centre of origin and diversification for the species of the group. Any other hypothesis on the natural history of the genus Chirocephalus should be set aside pending for a revision of the phylogeny of the genus.…”
Section: Brief Remarks On the Genus Chirocephalus In Turkeymentioning
confidence: 39%
See 3 more Smart Citations
“…Four species were attributed to the bairdi species-group, the remaining were attributed to the diaphanus species-group or are impossible to be attributed to any of the traditional species-groups (present work). The present work questions the monophyly of the bairdi species-group, thus calling into question also the hypothesis raised by Cottarelli et al (2007Cottarelli et al ( , 2010, who suggested the role of Asiatic Turkey as a possible centre of origin and diversification for the species of the group. Any other hypothesis on the natural history of the genus Chirocephalus should be set aside pending for a revision of the phylogeny of the genus.…”
Section: Brief Remarks On the Genus Chirocephalus In Turkeymentioning
confidence: 39%
“…In particular, Brtek (1995) divided Chirocephalus into five speciesgroups based on morphology, namely diaphanus, bairdi, spinicaudatus, Pristicephalus, and sinensis. Among these, the species-groups diaphanus-, bairdi-, and spinicaudatus-have been accepted and widely used in the recent literature (Brancelj & Gorjanc, 1999;Brtek & Cottarelli, 2006;Cottarelli et al, 2007Cottarelli et al, , 2010Ketmaier et al, 2003Ketmaier et al, , 2012. Conversely, the Pristicephalus and sinensis species-groups proved to be quite controversial, as Brtek (1995) stressed.…”
Section: The Chirocephalus Species-groupsmentioning
confidence: 99%
See 2 more Smart Citations
“…In more than four decades of activity, Graziella Mura described six anostracan species (Cottarelli & Mura, 1975Cottarelli et al, 2007Cottarelli et al, , 2010, and produced pioneer works on anostracan taxonomy, ecology and faunistics. In particular, she increased our knowledge on the importance and significance of anostracan egg morphology (e.g.…”
mentioning
confidence: 99%